ANALISIS RISIKO COLD CHAIN DALAM DISTRIBUSI VAKSIN COVID-19 DI WILAYAH BANDUNG MENGGUNAKAN PENDEKATAN FMEA DAN SWOT - Wynda Gerika Panjaitan; Riskita Farida Sihaloho; Cindy Kharina Khafur; Muhammad Yogi Firmansyah (CV. Denasya Smart Publisher, 2026)
The distribution of COVID-19 vaccines requires a cold chain system to maintain temperature stability and vaccine effectiveness. However, in practice, this system is vulnerable to various risks, especially in densely populated areas such as Bandung. This study aims to analyze the risks in the cold chain system for COVID-19 vaccine distribution in the Bandung area using the Failure Mode and Effect Analysis (FMEA) and SWOT Analysis approaches, based on a retrospective study using secondary data. The FMEA results show three high-priority risks: (1) power outages during storage (RPN = 216), (2) operational errors by officers (RPN = 192), and (3) damage to portable cooling devices (RPN = 192). The SWOT analysis revealed Strengths in inter-agency coordination, but the main Weaknesses lie in uneven cooling infrastructure and limited human resources. This study recommends technology-based mitigation (such as IoT for real-time temperature monitoring), regular training, and improvements to logistics infrastructure. These findings provide practical contributions to planning a more resilient vaccine distribution system in the face of future health emergencies